Networks, frictions and war machines: methodological notes on the Ukrainian crisis - Fadieiev, Volodymyr (Skhid, 2015)
Study of the current Ukrainian sociopolitical crisis requires addressing a number of epistemological obstacles. This is possible due to the use of methodological tools that can take into account the features of the studied object. A feature of the crisis of social processes is that they take place in the conditions of the loss of state monopoly on the legitimate use of violence. Anti-government protests in the Maidan and armed conflict in the east of Ukraine led to the emergence of many paramilitary social formations, are actively involved in social conflicts. The paper attempts to study the possibility of using the network theory to investigate the processes of the mobilization and formation of paramilitary formations. Additional theoretical module network theory performs the concept of "war machine." The author tries to describe this concept by means of the most important properties of the studied social objects. The study of the Ukrainian crisis in perspective network theory facilitates redirect research in a more pragmatic direction. According to the author, this approach provides a productive analytical tools for the study of actual social processes and facilitates finding ways out of this situation.